So the initial equation is:
![8x^2+8x=-2](https://img.qammunity.org/2023/formulas/mathematics/college/xymryx47g7ws3395fif9dwf9on9u7lkj0w.png)
To writte the equation in the standard form we have to make it equal to 0, so we can add 2 in bout sides of the equation:
![\begin{gathered} 8x^2+8x+2=-2+2 \\ 8x^2+8x+2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vpb1d2s6c634dtd09ozk535gugyv0q2clu.png)
now, (a) is the number thas goes with the x^2, (b) is the number that goes with the x and (c) is the number that is alon, so:
![\begin{gathered} a=8 \\ b=8 \\ c=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/chz7t71fxm4iq7d0b1rtplzmxai37oomld.png)
Now we can substitute this numbers in the quadratic equation:
![\begin{gathered} \frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \frac{-8\pm\sqrt[]{8^2-4(8)(2)}}{2(8)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/84c9drnj037dr9mfi3smqximp0l8ffhgky.png)
and finally we can simplify the equation:
![\begin{gathered} \frac{-8\pm\sqrt[]{64-64}}{16} \\ (-8)/(16)=(-4)/(8)=(-2)/(4)=-(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pxspi2ajc2loxrn68n6ga3u88fko7dnnte.png)